Attitudes of Lebanese secondary school English teachers towards English language, English teaching, and American culture - Lufti Diab, Rula (1996)
The purpose of this study was to investigate the attitudes of the English teachers in the private English-medium secondary schools in Beirut towards the English language, English teaching, and (American) English culture. A secondary purpose of the study w